DIALEKTIKA SNP DAN PROFESIONALISME ADAPTIF TENAGA KEPENDIDIKAN DI ERA DIGITAL - Nadila Shafa Khairunisa; Siti Aimah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze the dialectics of Natial Education Standards (NES) in shaping the adaptive professionalism of education personnel in the digital era. This research is crucial because the digital transformation of education requires education personnel to possess not only administrative skills but also technological competencies, work innovation, and the ability to adapt to changes in the modern education system. The method used was a qualitative one with a single case study design through in-depth interviews, observations, and document reviews. The results indicate that the NES serves as a normative framework in encouraging adaptive professionalism among education personnel, despite challenges such as low digital literacy, work culture resistance, and limited institutional infrastructure. This research contributes to strengthening the study of education personnel professionalism in the context of ongoing digital education transformation.